2023
DOI: 10.3390/genes14051038
|View full text |Cite
|
Sign up to set email alerts
|

Historical Mitogenomic Diversity and Population Structuring of Southern Hemisphere Fin Whales

Abstract: Fin whales Balaenoptera physalus were hunted unsustainably across the globe in the 19th and 20th centuries, leading to vast reductions in population size. Whaling catch records indicate the importance of the Southern Ocean for this species; approximately 730,000 fin whales were harvested during the 20th century in the Southern Hemisphere (SH) alone, 94% of which were at high latitudes. Genetic samples from contemporary whales can provide a window to past population size changes, but the challenges of sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 113 publications
1
8
1
Order By: Relevance
“…The topology of the phylogeny inferred from the mitochondrial genome sequences in this study largely agrees with earlier studies based on mitochondrial genome sequences, some of which were complemented with a few nuclear loci (Archer et al, 2013;Bérubé et al, , 2002Buss et al, 2023;Cabrera et al, 2019;Pérez-Alvarez et al, 2021). In agreement with the work by Cabrera and co-workers (2019), the new mitochondrial genome haplotypes detected in this study revealed all ocean basins to be polyphyletic or paraphyletic, likely a result of the increased sample sizes.…”
Section: Phylogeographic Structuresupporting
confidence: 91%
See 4 more Smart Citations
“…The topology of the phylogeny inferred from the mitochondrial genome sequences in this study largely agrees with earlier studies based on mitochondrial genome sequences, some of which were complemented with a few nuclear loci (Archer et al, 2013;Bérubé et al, , 2002Buss et al, 2023;Cabrera et al, 2019;Pérez-Alvarez et al, 2021). In agreement with the work by Cabrera and co-workers (2019), the new mitochondrial genome haplotypes detected in this study revealed all ocean basins to be polyphyletic or paraphyletic, likely a result of the increased sample sizes.…”
Section: Phylogeographic Structuresupporting
confidence: 91%
“…We were unable to detect any well-supported subclades among samples from the Southern Ocean in the phylogeny estimated from the whole autosomal genomes in agreement with (Buss et al, 2023;Pérez-Alvarez et al, 2021). However, the samples from the Southern Ocean in our study were restricted to the western Antarctic Peninsula and may not adequately capture the overall intra-oceanic genetic variance.…”
Section: Phylogeographic Structurecontrasting
confidence: 69%
See 3 more Smart Citations